Les deux manières d’expliquer la réalité proposées par Parménide - Cordero, Nestor Luis (Wydział Filozoficzny UAM, 2022)
Towards the end of fragment 1 of his Poem, Parmenides puts forward two methods or paths that a priori explain the same object of study: the existence of the fact or state of being. One of the options leads to the core of the truth and is, therefore, pursued. The other is merely a set of contradictory opinions and is, accordingly, abandoned. These two paths are expounded in the rest of the Poem, while fragment 4 shows that even the erroneous conception, which had to be set aside, can still be fruitful. Once the firm foundation of truth has been established, fragments 10 and 11 propose to widen the inquiry to the whole of reality. This interpretation suggests a rejection of the arrangement of the Poem that has become canonical, and a criticism of the doxographic tradition that since Aristotle has “Platonised” the philosophy of Parmenides by assimilating the “opinions” (which are only points of view) to the “appearances” (in the Platonic sense of the term).
Keywords: Truth; Opinions; Doxography; Fülleborn; Simplicius; Plato; Being; Parmenides